Financial frictions and optimal monetary policy in an open economy - Marcin Kolasa; Giovanni Lombardo (European Central Bank (ECB), 2011)
A growing number of papers have studied positive and normative implications of financial frictions in DSGE models. We contribute to this literature by studying the welfare-based monetary policy in a two-country model characterized by financial frictions, alongside a number of key features, like capital accumulation, non-traded goods and foreign-currency debt denomination. We compare the cooperative Ramsey monetary policy with standard policy benchmarks (e.g. PPI stability) as well as with the optimal Ramsey policy in a currency area. We show that the two-country perspective offers new insights on the trade-offs faced by the monetary authority. Our main results are the following. First, strict PPI targeting (nearly optimal in our model if credit frictions are absent) becomes excessively procyclical in response to positive productivity shocks in the presence of financial frictions. The related welfare losses are non-negligible, especially if financial imperfections interact with nontradable production. Second, (asymmetric) foreign currency debt denomination affects the optimal monetary policy and has important implications for exchange rate regimes. In particular, the larger the variance of domestic productivity shocks relative to foreign, the closer the PPI-stability policy is to the optimal policy and the farther is the currency union case. Third, we find that central banks should allow for deviations from price stability to offset the effects of balance sheet shocks. Finally, while financial frictions substantially decrease attractiveness of all price targeting regimes, they do not have a significant effect on the performance of a monetary union agreement.
Keywords: E52; E61; E44; F36; F41; 330; Financial Frictions; open economy; optimal monetary polic